A hybrid fuzzy multi-criteria decision-making approach for performance analysis and evaluation of park-level integrated energy system. (1st December 2019) - Zhou, Jianli; Wu, Yunna; Wu, Chenghao; Deng, Zhongqing; Xu, Chuanbo; Hu, Yong
Highlights: A practical framework is proposed to analyze and evaluate the overall performance. Performance analysis criteria and associated calculation model are determined. Appropriate fuzzy theory is used to improve the process of data processing and analysis. The realistic application state of TODIM method is expanded through scenario analysis. The results show that the wind-gas complementary scheme has an outstanding performance. Abstract: This paper aims to promote the further healthy development of integrated energy system (IES) through comprehensive performance analysis and evaluation. Firstly, the criteria system for performance analysis and evaluation is constructed, including economy, environment, energy utilization, reliability and sustainability. Correspondingly, the calculation models of quantitative criteria are defined in detail. Secondly, quantitative and qualitative data are obtained by the calculation models and hesitant fuzzy linguistic term sets, respectively. Then, the causality and the subjective weights of criteria are analyzed based on the intuitionistic fuzzy decision-making trial and evaluation laboratory method. The objective weight is calculated by entropy method. Finally, the schemes are evaluated based on the extended TODIM (an acronym in Portuguese of interactive and multi-criteria decision-making) method. The results show that the wind-gas complementary scheme A3 has the best overall performance. Furthermore, the result of scenario analysis shows that the TODIM method should set different regression coefficients to reflect the preferences of decision makers. Sufficient sensitivity analysis proves the stability and reliability of the model used in this paper; comparative analysis results show that the model has good applicability. This study provides comprehensive and quantifiable information support for integrated energy suppliers and expands the methods and applications in decision-making field.